Role of norepinephrine & angiotensin II in the neural control of renal sodium & water handling in spontaneously hypertensive rats - Salman, I.M.; Sattar, M.A.; Ameer, O.Z.; Abdullah, N.A.; Yam, M.F.; Salman, H.M.; Khan, M.A.H.; Johns, E.J. (Medknow Publications, 2010)
Background & objectives: A wealth of information concerning the essential role of renal sympathetic nerve activity (RSNA) in the regulation of renal function and mean arterial blood pressure homeostasis has been established. However, many important parameters with which RSNA interacts are yet to be explicitly characterized. Therefore, the present study aimed to investigate the impact of acute renal denervation (ARD) on sodium and water excretory responses to intravenous (iv) infusions of either norepinephrine (NE) or angiotensin II (Ang II) in anaesthetized spontaneously hypertensive rats (SHR). Methods: Anaesthetized SHR were acutely denervated and a continuous iv infusion of NE (200 ng/min/kg) or Ang 11 (50 ng/min/kg) was instigated for 1 h. Three 20-min urine clearances were subsequently collected to measure urine flow rate (UV) and absolute sodium excretion (U(Na)V). Results: Higher UV and U(Na)V (P<0.05) were observed in denervated control SHR as compared to innervated counterparts. The administration of NE or Ang II to innervated SHR produced lower UV and U(Na)V (P<0.05 vs. innervated control SHR). Lower diuresis/natriuresis response to ARD was observed in NE-treated SHR compared to denervated control SHR (P<0.05). Salt and water excretions in denervated NE-treated SHR, however, were significantly higher (P<0.05) relative to the excretion levels in control denervated SHR. Conversely, there was a higher (all P<0.05) diuresis/natriuresis response to ARD when Ang II was administered to SHR compared to denervated control or innervated Ang H-treated SHR. Interpretation & conclusions: NE retains its characteristic antidiuretic/antinatriuretic action following ARD in SHR. Typical action of Ang II on salt and water excretions necessitates the presence of an intact renal innervation. Ang II is likely to facilitate the release of NE from renal sympathetic nerve terminals through a presynaptic site of action. Moreover, there is a lack of an immediate enhancement in the renal sensitivity to the actions of NE and Ang II following ARD in a rat model of essential hypertension.